2020
DOI: 10.1186/s12929-019-0595-9
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Circular RNA circ_0003204 inhibits proliferation, migration and tube formation of endothelial cell in atherosclerosis via miR-370-3p/TGFβR2/phosph-SMAD3 axis

Abstract: Background: Circular RNAs (circRNAs) represent a class of non-coding RNAs (ncRNAs) which are widely expressed in mammals and tissue-specific, of which some could act as critical regulators in the atherogenesis of cerebrovascular disease. However, the underlying mechanisms by which circRNA regulates the ectopic phenotype of endothelial cells (ECs) in atherosclerosis remain largely elusive. Methods: CCK-8, transwell, wound healing and Matrigel assays were used to assess cell viability, migration and tube formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
80
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 43 publications
(53 reference statements)
9
80
0
Order By: Relevance
“…These results suggested that circ_0010283 may regulate the progression of atherosclerosis by sponging miR-370-3p. In addition, the inhibitory role of miR-370-3p in atherosclerosis progression was observed, which was consistent with previous studies (19,32).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results suggested that circ_0010283 may regulate the progression of atherosclerosis by sponging miR-370-3p. In addition, the inhibitory role of miR-370-3p in atherosclerosis progression was observed, which was consistent with previous studies (19,32).…”
Section: Discussionsupporting
confidence: 92%
“…For example, Zhang et al (16) have demonstrated that miR-370-3p is associated with acute pneumonia, and Hou et al (17) have reported that miR-370-3p suppresses VSMc viability in cerebral aneurysm. In addition, circ_0003204 can directly target miR-370-3p to repress the progression of atherosclerosis (32). In the present study, miR-370-3p was downregulated in ox-LdL-induced VSMcs compared with non-induced cells, and was negatively modulated by circ_0010283.…”
Section: Discussionsupporting
confidence: 51%
“…13 Increasing evidence has indicated that circRNAs play a crucial role including carcinogenesis, progression and clinical outcomes of various human cancers. 14,15 For example, researchers have found that circEPSTI1 could promote cell proliferation and apoptosis through sponging miR-4753 and miR-6809 to regulate the BCL11A level in triple-negative breast cancer. 16 The circNT5E could function as a sponge for the miR-422a, which is involved in cell proliferation, migration, and invasion in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…It is understood that circRNAs are involved in numerous pathological mechanisms underlying cVds, such as AS, immune response, apoptosis, cell proliferation, autophagy, cell senescence and myocardial repair (103)(104)(105)(106)(107)(108)(109). Emerging evidence has suggested that circRNAs play an important role in the occurrence and development of cVd (110).…”
Section: Regulatory Mechanisms Of Circrnas On Cvdmentioning
confidence: 99%